Implant Failure and Acetabular Protrusion Post Austin Moore Prosthesis: A Case Report - Bagus Meurah Suropati; Bagus Wibowo Soetojo; Rakha Rahmatullah Ibrahim; Totot Mudjiono (Universitas Muhammadiyah Surabaya, 2025)
Implant failure and acetabular protrusion are significant complications following Austin Moore prosthesis insertion, particularly in elderly patients with hip fractures. Total hip arthroplasty (THA) offers superior outcomes compared to hemiarthroplasty (HA) but comes with its own set of challenges. Understanding the risk factors and implications of these complications is crucial for choosing effective management. In this article, we report a 76-year-old woman who presented with severe left hip pain post-fall, eight years after HA with an Austin Moore prosthesis due to a trochanter fracture. The patient was able to walk with a walker before the fall. Physical examination revealed tenderness and limited range of motion. Radiographic imaging confirmed acetabular protrusion and AMP neck fracture. Conversion to THA using a hybrid system was performed successfully, with the patient exhibiting no post-operative complications. This case report showed that implant failure and acetabular protrusion pose complex challenges, exacerbated by patient demographics, implant design, and bone quality. THA emerges as a preferred option due to its superior outcomes, although conversion from HA is associated with increased risks. Early diagnosis and intervention, as well as a multidisciplinary approach and careful consideration of patient-specific factors, are crucial for optimizing patient outcomes and quality of life.